In vitro efficacy testing of citronella grass oil against Tritrichomonas foetus trophozoites - Ramirez, María Rosana; Sereno Bruno, Estefanía; Manuale, Debora; Yori, Juan Carlos; Oyhenart, Jorge (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2024)
Tritrichomonas foetus, a sexually transmitted parasitic protozoan, causes abortion in cattle. Nitroimidazoles, such as metronidazole, treat bovine trichomonosis, but their use is precluded. Plant extracts might have antiparasitic effects. This study aimed to assess Cymbopogon nardus oil activity against T. foetus as an alternative to metronidazole. T. foetus trophozoites were incubated in culture medium containing serial dilutions of C. nardus oil. Cytotoxicity was assessed 24 hours later. C. nardus oil killed T. foetus cells. Half maximal effective concentration (EC50) was 0.4 μg/mL. These findings suggest that C. nardus oil could be exploited for discovery and compound isolation of plant derived phytopharmaceuticals for bovine trichomoniasis and other protozoan diseases. Highlights: Tritrichomonas foetus causes abortion in cattle. Effective drugs are available but treatment is precluded. Cymbopogon nardus oil kills foetus trophozoites in a dose-dependent manner. Plant derived material could be used for bovine trichomonosis and other protozoan diseases.